Faktor Penentu Tingkat Literasi Keuangan Para Pengguna Kartu Kredit di Indonesia - Farah Margaretha; Siti May Sari (Universitas Muhammadiyah Yogyakarta, Indonesia, 2015)
The objectives of this research is to determine whether there are any significant differences between male’s and female’s financial literacy and whether age, educational level and income level also playing significant role in shaping credit card users’ financial lieracy. Using Anova test to verify the influence of age level, educational level and income level toward financial literacy. The result of this research conclude that there are no significant differences between male’s and female’s financial literacy. It is verified that there are significant influences between age, education, income toward credit card users’ financial literacy. Implication of this research is the share holder such as government, university, and bank more concern to make education and training to improve financial literacy of credit card user.